Arah Baru Kajian Pendidikan Sejarah Kebudayaan Islam Dari Muhammad Abid Jabiri - Muhammad Nasrudin; Fattah S Santoso; Triwahyu Budiutomo; Anggar Kaswati (Universitas Cokroaminoto Yogyakarta, 2022)
Muhammad Abid Jabari as a leading scholar in studying the historical development of Arab Islam that developed in the contemporary era. Abid al-Jabri by following modern steps in reading the history of Islam in the Arab Region in the Middle East region through his criticism of Arabic Reason. This historical research is approached philosophically historically to be able to formulate important ideas in reading SKI material that is in accordance with modern ideas in order to attract the students. Paradigm becomes an inevitable choice, because it is able to cover everything related to the source of knowledge. Abid Jabiri tried to base science with three epistemologies, the epistemology of Bayani logic, the epistemology of Burhani's logic and the epistemology of Irfani's reasoning, which became Islamic epistemological reasoning. Even though he received criticism from various directions, at least Jabiri was able to build a rational reading discourse according to the demands of the modern era, especially from the material side.